Helicobacter pylori PqqE is a new virulence factor that cleaves junctional adhesion molecule A and disrupts gastric epithelial integrity. (1st January 2021) - Marques, Miguel S.; Costa, Ana C.; Osório, Hugo; Pinto, Marta L.; Relvas, Sandra; Dinis-Ribeiro, Mário; Carneiro, Fátima; Leite, Marina; Figueiredo, Ceu
ABSTRACT: Helicobacter pylori infects approximately half of the world's population and is the strongest risk factor for peptic ulcer disease and gastric cancer, representing a major global health concern. H. pylori persistently colonizes the gastric epithelium, where it subverts the highly organized structures that maintain epithelial integrity. Here, a unique strategy used by H. pylori to disrupt the gastric epithelial junctional adhesion molecule-A (JAM-A) is disclosed, using various experimental models that include gastric cell lines, primary human gastric cells, and biopsy specimens of infected and non-infected individuals. H. pylori preferentially cleaves the cytoplasmic domain of JAM-A at Alanine 285. Cells stably transfected with full-length JAM-A or JAM-A lacking the cleaved sequence are used in a range of functional assays, which demonstrate that the H. pylori cleaved region is critical to the maintenance of the epithelial barrier and of cell-cell adhesion. Notably, by combining chromatography techniques and mass spectrometry, PqqE (HP1012) is purified and identified as the H. pylori virulence factor that cleaves JAM-A, uncovering a previously unreported function for this bacterial protease. These findings propose a novel mechanism for H. pylori to disrupt epithelial integrity and functions, breaking new ground in the understanding of the pathogenesis of this highly prevalent and clinically relevant infection.